1995
DOI: 10.1007/bf00925707
|View full text |Cite
|
Sign up to set email alerts
|

Role of DL ?-lipoic acid in gentamicin induced nephrotoxicity

Abstract: The effect of DL alpha-lipoic acid on the nephrotoxic potential of gentamicin was examined. Intraperitoneal injection of gentamicin (100 mg/kg/day) to rats resulted in decreased activity of the glycolytic enzymes-hexokinase, phosphoglucoisomerase, aldolase and lactate dehydrogenase. The two gluconeogenic enzymes--glucose-6-phosphatase and fructose-1,6-diphosphatase, the transmembrane enzymes namely the Na+, K(+)-ATPase, Ca(2+)-ATPase, Mg(2+)-ATPase and the brushborder enzyme alkaline phosphatase, also showed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Glutathione (GSH) and its redox cycle enzymes e.g., SOD, catalase, GSH-Px are important cellular defense system against oxidative stress. It has been reported that GM suppresses antioxidant defense enzymes and increases lipid peroxidation in the kidney (Ali and Bashir, 1996;Parlakpinar et al, 2004;Sandhya et al, 1995). The present results confirm earlier findings (Walker et al, 1999;Yazar et al, 2003;Karahan et al, 2005) and show that GM administration to normal rats caused severe damage to renal tissues most likely by ROS mediated mechanism as evident by decreased activities of above antioxidant enzymes and total SH levels that led to increased lipid peroxidation (LPO).…”
Section: Discussionsupporting
confidence: 95%
“…Glutathione (GSH) and its redox cycle enzymes e.g., SOD, catalase, GSH-Px are important cellular defense system against oxidative stress. It has been reported that GM suppresses antioxidant defense enzymes and increases lipid peroxidation in the kidney (Ali and Bashir, 1996;Parlakpinar et al, 2004;Sandhya et al, 1995). The present results confirm earlier findings (Walker et al, 1999;Yazar et al, 2003;Karahan et al, 2005) and show that GM administration to normal rats caused severe damage to renal tissues most likely by ROS mediated mechanism as evident by decreased activities of above antioxidant enzymes and total SH levels that led to increased lipid peroxidation (LPO).…”
Section: Discussionsupporting
confidence: 95%
“…Experimental studies demonstrated that ALA supplementation might decrease renal expression of endothelin-1 [109], fibronectin and collagen IV [110]. The protective influence of ALA against aminoglycoside-, and cisplatin-induced nephrotoxicity was shown in animal studies [111,112]. ALA was also found to attenuate deterioration of renal function in a model of ischemia/reperfusion injury [109].…”
Section: Alpha-lipoic Acidmentioning
confidence: 94%
“…Aminoglycoside antibiotics impair the function of mitochondrial enzymes for the gluconeogenesis, ammoniagenesis, and tricarboxylic acid oxidation pathways 21,22 ; in addition aminoglycoside antibiotics also downregulate the sodium-dependent glucose transport system 23,24 and reduce mRNA expression and protein levels of serum glutamate transaminase 1. This reduced reabsorption of glucose, resulting in increased urinary glucose excretion.…”
Section: Discussionmentioning
confidence: 99%